2008
DOI: 10.4162/nrp.2008.2.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seaweed supplementation on blood glucose concentration, lipid profile, and antioxidant enzyme activities in patients with type 2 diabetes mellitus

Abstract: The present study was carried out to evaluate the physiological effects of seaweed supplementation on blood glucose levels, lipid profile, and antioxidant enzyme activities in subjects with type 2 diabetes mellitus. Subjects were randomized into either a control group or a seaweed supplementation group. Pills with equal parts of dry powdered sea tangle and sea mustard were provided to the seaweed supplementation group three times a day for 4 weeks. Total daily consumption of seaweed was 48 g. We found that tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 38 publications
5
121
0
3
Order By: Relevance
“…ALP Alkaline phosphatase, ALT Alanine aminotransferase, AST Aspartate aminotransferase treatment groups was better than that in control fish on days 1 and 4 even though slight increase in antioxidant activity was noted in the group received the highest dose of the alga (10 g kg -1 ) on day 1. Such increase in antioxidative activity was shown in different animals fed on other dietary products containing astaxanthin (Nakano et al 1999;Pan et al 2003;Kim et al 2008). Kamath et al (2008) also showed that astaxanthin derived from H.p protects gastric mucosal injury by antioxidative mechanism in rats.…”
Section: Discussionmentioning
confidence: 82%
“…ALP Alkaline phosphatase, ALT Alanine aminotransferase, AST Aspartate aminotransferase treatment groups was better than that in control fish on days 1 and 4 even though slight increase in antioxidant activity was noted in the group received the highest dose of the alga (10 g kg -1 ) on day 1. Such increase in antioxidative activity was shown in different animals fed on other dietary products containing astaxanthin (Nakano et al 1999;Pan et al 2003;Kim et al 2008). Kamath et al (2008) also showed that astaxanthin derived from H.p protects gastric mucosal injury by antioxidative mechanism in rats.…”
Section: Discussionmentioning
confidence: 82%
“…However, Kim et al [43] reported that the diet of diabetic mice foods high in fiber and polyunsaturated fatty acids resulted in decreased levels of triglycerides, total cholesterol and LDL-C, although it was not effective in improving glycemic control. However, Raimondi et al [44] showed that nutritional counseling has a beneficial effect on the lipid profile and anthropometric parameters and the daily consumption of 40 g of oat bran provided an additional benefit in reducing insulin resistance parameters.…”
Section: Discussionmentioning
confidence: 99%
“…They documented that a 2.5-fold increase of seaweed consumption significantly lowered serum triglyceride and increased HDL cholesterol levels with no differences in LDL or total cholesterol levels (Kim et al, 2008). They documented that a 2.5-fold increase of seaweed consumption significantly lowered serum triglyceride and increased HDL cholesterol levels with no differences in LDL or total cholesterol levels (Kim et al, 2008).…”
Section: Seaweed Clinical or Epidemiological Studiesmentioning
confidence: 99%